Semiotika Sebagai Pendekatan Tafsirs: Telaah atas Pemikiran Mohammed Arkoun - Sufrianti Ramdhani; Muhammad Said Said (Alif Lam: Journal of Islamic Studies and Humanities, 2021)
Al-Qur'an al-Karim is an eternal Islamic miracle and its miracles are greatly strengthened by the evidence described through many approaches, one of which is the scientific approach and the semiotic approach. It was revealed by Allah to the Messenger of Allah to bring people out from darkness to light, and to guide them to the straight path. The research departs from the many developments of methods and approaches that are so diverse in the interpretation of the Qur'an, thus forming a debate among commentators. This study is essentially an attempt to find out how semiotics is a method of approaching interpretation in Arkoun's thinking and how to apply semiotics in the interpretation of the Qur'an. This study aims to answer these two problems, this research is a library research using qualitative methods and descriptive analysis, namely by reading it over and over again, then looking for various relevant literature sources. The data obtained will be analyzed according to scientific theories with the provisions in the analysis guidelines and according to the rules of the author of the scientific work used. The results show that semiotics, when associated with the Qur'an as a text manuscript (verses), then the Al-Qur'an is a holy book text that is packaged in Arabic which is a code or symbol that contains multiple dimensions of meaning. . Therefore, the Qur'an as an Arabic text is a series of signs that can be studied, analyzed and interpreted using a semiological approach. That is why, the Qur'an in semiotics is the basic units called sign verses). Signs in the Qur'an are not only the smallest parts of its elements, such as: letters, words and sentences, but the totality of structures that connect each element is included in the category of signs of the Qur'an. This shows that the entire existence of the Qur'an is a series of signs that have meaning.